Potensi precision farming dalam penerapan prinsip reduce untuk mengurangi limbah sumber daya pertanian - Undari, Desti; Arista, Nor Isnaeni Dwi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The increase in agricultural production is often accompanied by excessive use of chemical inputs, contributing to environmental pollution. Precision farming is a modern approach that can address this challenge by optimizing input use through advanced technology. This paper explores the application of the reduce principle in precision farming to support efficient use of fertilizers and other resources. Method: The method used is a literature review of various published studies related to precision farming and agricultural land management. Findings: The application of the reduce principle in fertilization activities with precision farming can reduce fertilizer waste by up to 50%, increase land productivity by 10%, and minimize harmful environmental effects, such as groundwater pollution and greenhouse gas emissions. Precision farming also improves irrigation efficiency through precision irrigation technology. Conclusion: This study confirms that applying precision farming with a focus on the reduce principle not only supports sustainable agriculture but also provides economic benefits for farmers by reducing production costs. Innovations in precision farming technology, such as the integration of AI-based sensors and IoT, further enhance potential efficiencies in the future. Novelty/Originality of this article: Emphasizing the use of the reduce principle in precision farming as a primary strategy to achieve more efficient and environmentally friendly agriculture aligns with the goals outlined in the Sustainable Development Goals (SDGs) for responsible production.